PENGGUNAAN ALAT PERMAINAN EDUKATIF UNTUK MENINGKATKAN KREATIVITAS ANAK DI TK - Muyasaroh (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2013)
In the process of educating at TK (Primary School), one of the main goals is to develop the creativity of children optimally. It is so important about developing the creativity of children can be seen from the difference of the role of the teacher which is early dominating a class, now must give more a chance to the children to take a more active and creative role in the comfortable atmosphere and that is supported with supplying educative games. That dimension is underlying this research. This research heads for increasing the creativity of children through using the tools of educative games. Those tools which are used are origami paper, poster paint, and plastisin. The kind of this research is a research of class action, because this research is relevant and agrees with the object of research. The subject of this research is all of the pupils in group BI in TK ABA I Braja Harjosari, 32 Pupils. The collecting of data that is collected in this research is observation, interview/discussion, and documentation. This research is going to act in cycle I and II around six times meeting. After analyzing and working through in this research, the writer can take the conclusion that the using tools of educative games can increase the creativity of the children age 5-6 years. It can be proved with the percentage of !inal learning to cycle I up to 56, 25% and then increasing at the cycle II becomes 71, 87%